2014
DOI: 10.1088/1758-5082/6/2/024113
|View full text |Cite
|
Sign up to set email alerts
|

Bioreactor for modulation of cardiac microtissue phenotype by combined static stretch and electrical stimulation

Abstract: We describe here a bioreactor capable of simultaneously applying mechanical and electrical field stimulation in conjunction with static strain and on-line force of contraction measurements. It consisted of a polydimethylsiloxane (PDMS) tissue chamber and a pneumatically driven stretch platform. The chamber contained eight tissue microwells (8.05 mm in length and 2.5 mm in width) with a pair of posts (2.78 mm in height and 0.8 mm in diameter) in each well to serve as fixation points and for measurements of cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 48 publications
1
40
0
Order By: Relevance
“…The biowire maturation represented an intermediate phenotype as CMs undergo maturation from the embryonic state, as evidenced by low membrane conductance. The use of electrical stimulation in conjunction with stretch as a mimic of cardiac load, concurrently or sequentially, might be required to induce terminal differentiation and maturation in hiPSC-CMs [94, 95]. …”
Section: Biomaterials Used To Generate 3d Cardiac Modelsmentioning
confidence: 99%
“…The biowire maturation represented an intermediate phenotype as CMs undergo maturation from the embryonic state, as evidenced by low membrane conductance. The use of electrical stimulation in conjunction with stretch as a mimic of cardiac load, concurrently or sequentially, might be required to induce terminal differentiation and maturation in hiPSC-CMs [94, 95]. …”
Section: Biomaterials Used To Generate 3d Cardiac Modelsmentioning
confidence: 99%
“…The results indicate the importance of combined electromechanical simulation and the selection of appropriate timing for stimulation (97). Similarly, Miklas et al (98) combined electrical pacing with static stretching and found improved sarcomere structure and increased contractile force.…”
Section: Tissue Engineering and Biomaterials For The Restoration Omentioning
confidence: 97%
“…Electrical stimulation of these cell-laden structures led to increased myofibril organization and enhanced contractile and electrical properties compared to non-stimulated controls. Subsequent work, by the same group and others, has indicated that a combination of electrical stimulation and mechanical conditioning plays an important role in stem cell differentiation towards cardiac cells as well as cardiac tissue maturation (65, 66) . Biomaterials can contribute significantly to this effort by facilitating the integration of electrical and mechanical cues in 3D stem cell cultures (67) .…”
Section: Biomaterials Assisted 3d Tissue Formation Through Hpsc Difmentioning
confidence: 99%